PEMIKIRAN IBNU QAYYIM TENTANG RIBA DAN RELEVANSINYA TERHADAP PEREKONOMIAN DI INDONESIA - Nasiroh, Wilda; Rofi’ah, Khusniati (AMAL: Jurnal Ekonomi Syariah, 2023)
AbstractThis article focuses on Ibn Qayyim's thoughts on usury and its relevance to the economy in Indonesia. The type of research used in this article is library research. Library research is when researchers use books, journals, scientific magazines published by private or government institutions, published periodically (periodicals), yearbooks, annual reviews, magazines, newspapers, historical records, as the subject of study. Economic thought according to Ibn Qayyim is about Islamic economic philosophy, views on prosperity and poverty, the economic significance of charity (zakat), the prohibition of usury, and market mechanisms and price determination. According to Ibn Qayyim's view, usury is divided into two, namely, usury jali and usury khafi. Ibn Qayyim emphasized the prohibition of usury in Islam because of its potential to create economic inequality and compromise the welfare of society. This view remains relevant in the context of Indonesia struggling with significant economic inequality and the challenge of poverty alleviation. The way to overcome usury is through education and religious awareness, such as increasing religious education and public awareness about the prohibition of usury in Islam, developing sharia financial institutions, innovation in sharia financial products, and government commitment.Keywords: Usury, Economic Thought, Ibn Qayyim, Relevance.  AbstrakArtikel ini memfokuskan pada pemikiran Ibnu Qayyim tentang riba dan juga relevansinya terhadap perekonomian di Indonesia. Jenis penelitian yang digunakan pada artikel ini yaitu penelitian pustaka (Library research). Penelitian pustaka adalah apabila peneliti menjadikan buku, jurnal, majalah ilmiah terbitan lembaga swasta ataupun pemerintah, diterbitkan berkala (periodical), yearbook, annual review, majalah, surat kabar, catatan historis, sebagai pokok kajian. Pemikiran ekonomi menurut Ibnu Qayyim yaitu tentang falsafah ekonomi islam, pandangan tentang kemakmuran dan kemiskinan, signifikansi ekonomi dalam amal zakat (zakat), larangan riba, dan mekanisme pasar dan penetapan harga. Menurut pandangan Ibnu Qayyim riba dibagi menjadi dua yaitu, riba jali dan riba khafi. Ibnu qayyim menekankan larangan riba dalam islam karena potensinya untuk menciptakan ketidaksetaraan ekonomi dan mengorbankan kesejahteraan masyarakat. Pandangan ini tetap relevan dalam konteks Indonesia yang berjuang melawan ketidaksetaraan ekonomi yang signifikan dan tantangan pengentasan kemiskinan. Untuk cara menanggulangi riba yaitu dengan pendidikan dan kesadaran agama, seperti meningkatkan pendidikan agama dan kesadaran masyarakat tentang haramnya riba dalam islam, pengembangan lembaga keuangan syariah, inovasi produk keuangan syariah, dan komitmen pemerintah.Kata Kunci: Riba, Pemikiran Ekonomi, Ibnu Qayyim, Relevansi.